Influência da variação de umidade pós-compactação na deformabilidade de um solo argiloso laterítico empregado como subleito rodoviário - Koch, Taline (2024)
The pavement’s subgrade that presents construction efficiency, compacted in terms of optimum moisture content, maximum dry apparent specific weight and with good drainage, tends to lose moisture over time and remain in balance. In this situation where the soil does not reach saturation, its behavior is governed by the theory of unsaturated soils, and suction is an important parameter for understanding this behavior. However, the entrance of water into the subgrade can occur through several mechanisms, such as infiltrations or drainage failures. These variations in subgrade moisture content can influence its performance and, consequently, the entire pavement structure. Therefore, this research aims to verify the influence of post-compaction moisture variation and the effect of matric suction on the susceptibility to deformability of a subgrade soil on the RS-344 state highway located in the northwest of Rio Grande do Sul. The material analysis used knowledge of Pavement Mechanics and the concepts of Unsaturated Soil Mechanics. The experimental program aimed to carry out physical, chemical, mineralogical and hydromechanical characterization tests. The effects of moisture on soil deformability were evaluated under three conditions: optimal moisture content and varying the post-compaction humidity by ±2% of the optimal content, through drying and moistening the samples. It was verified through the triaxial repeated load tests found that drying tends to increase resilience modulus values and reduce permanent deformations considerably, regardless of the stress state tested, while moistening leads the soil to show an opposite response. This demonstrates that the increase in matric suction is related to an increase in soil performance in relation to the deformations investigated. None of the moisture conditions analyzed would eliminate the soil from being used as a road subgrade material through the shakedown analysis, but attention is needed in the occurrence of water access, which can lead to the soil collapsing and not to accommodate the deformations, depending on the load loads imposed. Additionally, simulations were carried out in the MeDiNa program in order to evaluate such responses in the design of hypothetical pavements. It was possible to verify that by replacing the optimal parameters with the moistening parameters imposed for the soil, the pavement responds with an increase in permanent deformations and contributes to an increase in the percentage of cracked area of the surface layer in all simulations carried out. Drying caused the opposite effect, showing that with the possible equilibrium humidity below the optimum being reached, the pavement starts to have superior performance, highlighting the favorable action of suction in this condition. Finally, this research contributes to the hydromechanical knowledge of the soil presented, as well as contributing to the expansion of the MeDiNa database, mainly by investigating humidity levels beyond the optimum in post- compaction conditions where climatic variations and construction efficiency affect.